2009
DOI: 10.1016/j.schres.2009.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Deviant trajectories of cortical maturation in 22q11.2 deletion syndrome (22q11DS): A cross-sectional and longitudinal study

Abstract: 22q11.2 deletion syndrome (22q11DS) is associated with an increased susceptibility to develop schizophrenia. Despite a large body of literature documenting abnormal brain structure in 22q11DS, cerebral changes associated with brain maturation in 22q11DS remained largely unexplored. To map cortical maturation from childhood to adulthood in 22q11.2 deletion syndrome, we used cerebral MRI from 59 patients with 22q11DS, aged 6 to 40, and 80 typically developing controls; three year follow-up assessments were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
134
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 108 publications
(148 citation statements)
references
References 55 publications
14
134
0
Order By: Relevance
“…However, contrarily to our results that indicate a dysfunction predominantly located within the frontal lobes, morphometric studies usually describe a relative preservation of the frontal volume in the syndrome (Eliez et al 2000;Kates et al 2001Kates et al , 2004Simon et al 2005). Nevertheless, localized frontal gray matter alterations have also been described (Shashi et al 2010;van Amelsvoort et al 2001;Schaer et al 2009;Bearden et al 2007) notably in regions that have a high degree in our discriminative graph, such as superior, medial (Schaer et al 2009), and orbital (Bearden et al 2007) frontal regions. These morphological alterations could be related to the underlying disruption of the structural network (He et al 2007;Lerch et al 2006;Alexander-Bloch et al 2013) and could also affect the function of the frontal lobe and its interactions with the rest of the brain.…”
Section: Discriminating Patients With 22q11ds From Healthy Controlssupporting
confidence: 59%
“…However, contrarily to our results that indicate a dysfunction predominantly located within the frontal lobes, morphometric studies usually describe a relative preservation of the frontal volume in the syndrome (Eliez et al 2000;Kates et al 2001Kates et al , 2004Simon et al 2005). Nevertheless, localized frontal gray matter alterations have also been described (Shashi et al 2010;van Amelsvoort et al 2001;Schaer et al 2009;Bearden et al 2007) notably in regions that have a high degree in our discriminative graph, such as superior, medial (Schaer et al 2009), and orbital (Bearden et al 2007) frontal regions. These morphological alterations could be related to the underlying disruption of the structural network (He et al 2007;Lerch et al 2006;Alexander-Bloch et al 2013) and could also affect the function of the frontal lobe and its interactions with the rest of the brain.…”
Section: Discriminating Patients With 22q11ds From Healthy Controlssupporting
confidence: 59%
“…For instance, altered cortical thickness in the orbitofrontal cortex (Jalbrzikowski et al, 2013), volumetric reductions in the temporal lobe (Kates et al, 2011), and reductions in overall gyrification (Kunwar et al, 2012) have been related to positive symptoms in these patients. Cortical thickness reductions in left superior frontal gyrus and in the fusiform and lingual gyri have also been observed in patients with 22q11DS who have been diagnosed with schizophrenia compared to those who have not (Schaer et al, 2009). However, most of these findings refer mainly to positive symptoms.…”
Section: Introductionmentioning
confidence: 86%
“…The cross-sectional sample of patients with 22q11DS included in the analysis was collected in the context of a longitudinal study started in 2002 (Maeder et al, 2016;Schaer et al, 2009). Information regarding the selection of patients for this study, along with their demographic details, is reported in the Supplementary material.…”
Section: Participantsmentioning
confidence: 99%
“…Cognitive delay, as well as increased prevalence of attention deficits, mood and anxiety disorders, is characteristic of this population (De Smedt et al, 2007a;Green et al, 2009). Concern relating to psychological health in these adolescents is matched by the neuroscientists' efforts to identify the neural markers associated with early schizotypal trait expression in 22q11DS (Schaer et al, 2009a;Gothelf et al, 2011). Indeed, in this deletion syndrome where 25-30% are thought to evolve into formal schizophrenia spectrum disorders by adulthood (Murphy et al, 1999), neurodevelopment during adolescence may provide key insights to understanding the unfolding of psychotic symptoms.…”
Section: Introductionmentioning
confidence: 99%